Effect of Frequency of Subculturing of different Isolates of Beauveria bassiana Vuillemin on their Biological Properties - Rajanikanth, P.; Subbaratnam, G. V.; Rahaman, S. J. (International Journal of Bio-resource and Stress Management, 2023)
An experiment was conducted to find the effect of repeated subculturing on biological properties viz., radial growth, sporulation and conidial viability of four strains (Bb-13, Bb-11, Bb-5A and Bb-N) and two local isolates (Bb-L-1 and Bb-L-2) of Beauveria bassiana Vuillemin on synthetic media. The results of the experiment showed no significant reduction of the biological properties during the initial 1st to 7th subculturing but showed significant negative effects on the biological properties after 7th subculturing. Molecular characterization of the strains using PCR based RAPD indicated considerable variability among the isolates.